The Influence of Hemodialysis Services on Patient Satisfaction at Level III Hospital 06.03.01 Ciremai - Nining Wahyuni; Zuki Kurniawan; Rohadin Rohadin (Gema Wiralodra, 2025)
This study seeks to examine the impact of hemodialysis services on patient satisfaction at the 06.03.01 Ciremai Level III Hospital. Hemodialysis is a critical medical treatment that requires a high level of professionalism and rigorous quality standards, as it is directly associated with the safety and quality of life of individuals suffering from chronic kidney failure. High service quality not only reflects the hospital’s overall performance but also enhances patient confidence and contributes to the institution’s public image. The research applied a quantitative method using a descriptive and correlational approach. The population consisted of all 80 patients receiving hemodialysis therapy at Ciremai Hospital, with 44 respondents selected through accidental sampling. Data were collected using a questionnaire developed according to the SERVQUAL service quality framework, which includes five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The findings demonstrate that the quality of hemodialysis services has a positive and statistically significant influence on patient satisfaction. Correlation analysis produced a coefficient of 0.331 with a significance value of 0.015, indicating a moderate and positive relationship between service quality and satisfaction. This suggests that improvements in service delivery are associated with higher levels of patient satisfaction. Among the SERVQUAL dimensions, empathy and responsiveness were identified as the most influential factors, whereas tangibles showed the weakest effect. Overall, the study highlights the necessity of enhancing service quality, particularly in communication, prompt responsiveness, and individualized patient care. Hospitals are encouraged to further promote a culture of excellent service by providing continuous training for medical staff, upgrading supporting facilities, and implementing regular evaluations of service quality.